Effect of Selenium on the Iron Homeostasis and Oxidative Damage in Brain and Liver of Mice - Inga Staneviciene; Jurgita Sulinskiene; Ilona Sadauskiene; Arunas Liekis; Ausrine Ruzgaite; Rima Naginiene; Dale Baranauskiene; Vaida Simakauskiene; Raulas Krusnauskas; Dale Viezeliene (MDPI AG, 2022)
Selenium is an essential trace element that maintains normal brain function, mainly due its antioxidant properties. Although the amount of Se in the body is tightly regulated by the liver, both an excess of and deficiency in Se can modulate the cellular redox status and affect the homeostasis of other essential elements for both humans and animals. The aim of this study was to determine the effect of inorganic selenium excess on oxidative stress and iron homeostasis in brain and liver of laboratory BALB/c mice, which were supplemented with Na2SeO3 solution (0.2 mg and 0.4 mg Se/kg body weight) for 8 weeks. The content of the lipid peroxidation product malondialdehyde and antioxidant enzyme catalase activity/gene expression were used as markers of oxidative damage and were evaluated by spectrophotometric assays. Selenium and iron concentrations were determined by inductively coupled plasma mass spectrometry (ICP-MS). Catalase gene expression was analyzed by qRT-PCR and ΔΔCt methods. Our results showed that doses of 0.2 mg Se and 0.4 mg Se caused a relatively low accumulation of Se in the brain of mice; however, it induced a 10-fold increase in its accumulation in the liver and also increased iron accumulation in both tested organs. Both doses of Se increased the content of malondialdehyde as well as decreased catalase activity in the liver, while the 0.4 mg Se dose has also activated catalase gene expression. Brain of mice exposed to 0.2 mg Se showed reduced lipid peroxidation; however, the exposure to 0.4 mg of Se increased the catalase activity as well as gene expression. One may conclude that exposure to both doses of Se caused the accumulation of this micronutrient in mice brain and liver and have also provided a disrupting effect on the levels of iron. Both doses of Se have triggered oxidative liver damage. In the brain, the effect of Se was dose dependent, where −0.2 mg of Se provided antioxidant activity, which was observed through a decrease in lipid peroxidation. On the contrary, the 0.4 mg dose increased brain catalase activity as well as gene expression, which may have contributed to maintaining brain lipid peroxidation at the control level.